An analysis of impoliteness strategies on Donald Trump's tweets and reply posts of his tweets - Talia, Kiki Firginia (2020)
Since social media platforms, a forum for online interaction and communication, provide freedom to express opinions, responds, and criticizes other people or somethings freely, impolite utterances on social media are often found. This study intends for examining the use of impolite expressions on Twitter, focusing on impoliteness strategies on Donald Trump's tweets and reply posts of his tweets. This study attempts to determine the types of Culpeper's impoliteness strategies (1996) on four of Donald Trump's tweets and 244 replies of those four tweets. The findings indicate that impoliteness strategies are found on four of Donald Trump's tweets, and reply posts of those four tweets, including bald on record impoliteness, positive impoliteness, negative impoliteness, and sarcasm or mock politeness.